Complete mitochondrial genome sequencing and identification of candidate genes responsible for C5-type cytoplasmic male sterility in cabbage (B. oleracea var. capitata) - Zhong, Xionghui; Yue, Xiangqing; Cui, Jian; Han, Rui; Gao, Yi; Kang, Jungen (Frontiers in Plant Science, 2022)
Cytoplasmic male sterility (CMS) is widely used in cruciferous vegetables hybrid breeding. The C5-type CMS cabbage line exhibits stable male sterility and offers great value for cabbage breeding. However, the underlying CMS mechanism remains unclear. Here, the complete mitochondrial genome was sequenced and assembled for this line. The genome size was 221,862 bp. Mitochondrial genome comparison showed that the mitochondrial genome was likely generated by recombination with a nap-type CMS B. napus strain. Sixty-seven unknown-function open reading frames (ORFs) were identified. Seven orfs, orf114a, orf123a, orf188a, orf222a, orf261a, orf286a, and orf322a, were specifically identified in this genome. The presence of these candidate CMS genes decreased ATPase activity and ATP content by affecting the transcript levels of energy metabolism-related genes and F1F0-ATP synthase assembly. Among them, orf188a, orf222a, orf261a, orf286a, and orf322a possessed a transmembrane structure, and orf188a was cotranscribed with rps7 and trnfM. orf222a was partially homologous to atp8 and coexpressed with nad5. orf261a and orf322a were cotranscribed with cox1 and atp9, respectively. Additionally, orf114a was cotranscribed with atp8. Yeast two-hybrid assays showed that the ORF222a protein interacts with a B. oleracea ATP17 homolog (Bo7g114140) during F1F0-ATP synthase (F0-type ATP synthase, ATPase) assembly, reducing the quantity and activity of assembled F1F0-ATP synthase. Cytological sections showed that premature separation of the tapetum from the connective tissue and delayed tapetal programmed cell death (PCD) might be the immediate causes of CMS in C5-type CMS cabbage lines. Our results may help uncover the molecular mechanism of C5-type CMS in B. oleracea from the perspectives of the whole mitochondrial genome and cytology of anther development.